Acute mesenteric ischemia diagnosed via computed tomography in a dog following vehicular blunt force trauma: a Case Report - Altwal, Johnny; Guieu, Liz; Cook, Margaret; Warhoe, Jessie; Ray, Christopher; Hall, Kelly (Frontiers in Veterinary Science, 2025)
Acute mesenteric ischemia (AMI) refers to a group of vascular disorders that disrupt intestinal blood flow, resulting in intestinal ischemia and necrosis if left untreated. In both humans and dogs, this condition appears to be rare but deadly. There has only been one documented case of traumatic acute mesenteric ischemia in a dog, and the diagnosis was conducted through laparotomy. We present the case of a dog that was struck by a vehicle and subsequently developed traumatic acute mesenteric ischemia, which was diagnosed through computed tomography (CT). The dog presented with profuse hemorrhagic diarrhea, which persisted throughout the hospitalization. The dog’s condition eventually deteriorated as a result of diffuse intestinal ischemia, diagnosed using computed tomography (CT). Due to the anticipated poor prognosis, the dog was euthanized humanely. Traumatic acute mesenteric ischemia in dogs may be an underdiagnosed consequence of vehicular trauma, necessitating further diagnostic investigation in dogs with persistent gastrointestinal signs that are unresponsive to medical therapy.